2021
DOI: 10.1002/adsc.202001313
|View full text |Cite
|
Sign up to set email alerts
|

Engineering an Alcohol Dehydrogenase from Kluyveromyces polyspora for Efficient Synthesis of Ibrutinib Intermediate

Abstract: S)-N-Boc-3-hydroxypiperidine [(S)-NBHP] is a key intermediate for the synthesis of mantle cell lymphoma drug, ibrutinib. Here, KpADH, an alcohol dehydrogenase from Kluyveromyces polyspora, exhibits evolutionary potential in the asymmetric reduction of N-Boc-3-piperidone (NBPO) to (S)-NBHP. By screening key residues in substrate binding pocket of KpADH, an excellent variant Y127W was obtained with 6-fold improved activity of 119.3 U mg À 1 , 1.8-fold enhanced half-life of 147 h and strict S-stereoselectivity (>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…[16] N-Boc amine derivatives are key intermediates in synthesizing a number of commercially available drugs. For examples, N-Boc piperidine (3 a), N-Boc 4-chloropiperidine (3 e), N-Boc 4hydroxypiperidine (3 k), and N-Boc 3-hydroxypiperidine (3 q) are key intermediates for Ritalin, [17] Bepotastine, [18] Crizotinib, [19] and Ibrutinib, [20] respectively. Thus, we further illustrated the gramscale synthesis of various medically important N-Boc amines.…”
Section: Resultsmentioning
confidence: 99%
“…[16] N-Boc amine derivatives are key intermediates in synthesizing a number of commercially available drugs. For examples, N-Boc piperidine (3 a), N-Boc 4-chloropiperidine (3 e), N-Boc 4hydroxypiperidine (3 k), and N-Boc 3-hydroxypiperidine (3 q) are key intermediates for Ritalin, [17] Bepotastine, [18] Crizotinib, [19] and Ibrutinib, [20] respectively. Thus, we further illustrated the gramscale synthesis of various medically important N-Boc amines.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the higher substrate‐enzyme binding affinity mainly contributes to the increased catalytic efficiency ( k cat / K m ) of Km AKR M13 , attributing to the formation of more stable hydrogen bonds between Km AKR M13 and (5 S )‐CHOH. Similarly, the significant activity enhancement of the alcohol dehydrogenase from Kluyveromyces polyspora ( Kp ADH) was due to the additional hydrogen bonds formed between the Boc group of the substrate N‐Boc‐3‐piperidone (NBPO) and W127, which made the substrate‐enzyme binding more stable (Y. F. Wu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Structural analysis showed that the hydrogen bonds between Y64/H122 and (5S)-CHOH are shortened from 2.9 to 2.6Å to 2.5 and 2.2Å, respectively (Figure 8a binding more stable (Y. F. Wu et al, 2020).…”
Section: Asymmetric Reduction Of (5s)-choh To (3r5s)-cdhhmentioning
confidence: 99%
“…Additional hydrogen bonds were introduced by the Y127W mutation between the indole group of W127 and the Boc group of NBPO, favoring the reach of the catalytic conformation for nucleophilic attack in the reaction. The Kp ADH‐Y127W shows strict S ‐stereoselectivity (>99% ee ), and a 5.03‐fold higher specific activity (119.3 U mg −1 ) than that of the wild‐type (Wu et al, 2021).…”
Section: Application Cases Of Structure‐based Designmentioning
confidence: 99%